Principles of fraud examination - Wells, Joseph T. (Hoboken, N.J. : Wiley, 2011)
"Accountants need to have a strong understanding of fraud - what it is and how it is committed, prevented, and resolved. The third edition provides them with that knowledge. It documents the schemes used by executives, managers, and employees to commit fraud against their organisations. Case studies, complete with statistics and flowcharts, are provided for each chapter. A new chapter is included on fraud risk assessment. Updated statistics are presented on recent ACFE findings. In addition, minor revisions throughout focus on the increasing use of electronic payments and other technology in fraud schemes. This helps accountants detect and prevent fraud"--
Keywords: Fraud; Fraud investigation; Fraud -- Prevention; Auditing, Internal; BUSINESS & ECONOMICS / Auditing